Future-Proofing the Rural Broadband Workforce - Oates, Bryce (Rural Telecommunications, 2019)
According to Joshua Seidemann, vice president of policy for NTCA-The Aural Broadband Association, many rural telccs are working to address the same issue: how to best recruit and train the rural workforce of the future. The statewide trade association has forged a formal broadband technician skills and training partnership with the Wisconsin Indianhead Technical College (WITC) and Wisconsin Department of Workforce Development (DWD). The human resources manager said that she expects Twin Lakes to deepen this partnership with local workforce training efforts in the future. [...]FCC Chair Ajit Pai recently appointed WSTA to the commission's Broadband Deployment Advisory Committee Working Group on Job Skills and Training Opportunities.